Framing obesity in United Kingdom policy from the Blair years, 1997-2015. The persistence of individualistic approaches despite overwhelming evidence of societal and economic factors, and the need for collective responsibility - Ulijaszek, S; McLennan, A (Wiley, 2016)
Since 1997, and despite several political changes, obesity policy in the UK has overwhelmingly framed obesity as a problem of individual responsibility. Reports, policies and interventions have emphasized that it is the responsibility of individual consumers to make personal changes to reduce obesity. The Foresight Report‘Tackling Obesities: Future Choices’ (2007) attempted to reframe obesity as a complex problem that required multiple sites of intervention well beyond the range of personal responsibility. This framing formed the basis for policy and coincided with increasing acknowledgement of the complex nature of obesity in obesity research. Yet policy and interventions developed following Foresight, such as the Change4Life social marketing campaign, targeted individual consumer behaviour. With the Conservative-Liberal Democrat government of 2011, intervention shifted to corporate and individual responsibility, making corporations voluntarily responsible for motivating individual consumers to change. This article examines shifts in the framing of obesity from a problem of individual responsibility, towards collective responsibility, and back to the individual in UK government reports, policies and interventions between 1997 and 2015. We show that UK obesity policies reflect the landscape of policymakers, advisors, political pressures and values, as much as, if not more than, the landscape of evidence. The view that the individual should be the central site for obesity prevention and intervention has remained central to the political framing of population-level obesity, despite strong evidence contrary to this. Power dynamics in obesity governance processes have remained unchallenged by the UK government, and individualistic framing of obesity policy continues to offer the path of least resistance.